2005
DOI: 10.1016/j.aquabot.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in photosynthetic irradiance response curves of macrophytes from a Mediterranean coastal lagoon

Abstract: The main photosynthesis and respiration parameters (dark respiration rate, light saturated production rate, saturation irradiance, photosynthetic efficiency) were measured on a total of 23 macrophytes of the Thau lagoon (2 Phanerogams, 5 Chlorophyceae, 10 Rhodophyceae and 6 Phaeophyceae). Those measurements were performed in vitro under controlled conditions, close to the natural ones, and at several seasons. Concomitantly, measurements of pigment concentrations, carbon, phosphorous and nitrogen contents in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Our study, along with previous studies (Pihl et al, 1996;Plus et al, 2005; Sousa-Dias and Melo, 2008), has shown that macroalgal communities can have higher species richness and biomass in summer than in other seasons (Table 2; Fig.5). In summer, U lva pertusa was the dominant species along the Yantai coast (Table 3).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study, along with previous studies (Pihl et al, 1996;Plus et al, 2005; Sousa-Dias and Melo, 2008), has shown that macroalgal communities can have higher species richness and biomass in summer than in other seasons (Table 2; Fig.5). In summer, U lva pertusa was the dominant species along the Yantai coast (Table 3).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, many studies have found that Ulva sp. biomass peaked in spring and summer (Ferreira and Ramos, 1989;Solidoro et al, 1997;Plus et al, 2005). Zhuang and Chen (2003) found similar summer peaks in Moon Bay, near Fisherman's Wharf, on the Yantai coast.…”
Section: Discussionmentioning
confidence: 87%
“…No other paper on the potential use as a source of bioactive compounds of this species seems to be present in the literature. The positive results obtained in the present study could, therefore, represent a valid basis for the development of the research on C. linum, considering that this is usually a dominant species in the lagoon unattached communities in several world regions [29,30].…”
Section: Discussionsupporting
confidence: 56%
“…A 5‰ salinity is the smallest salinity amount compatible with seagrass development (Iversen, 1931 cited by Vermaat et al [23]; [24][25][26]), whereas seagrass communities can stand waters which are more salty than the global ocean salinity (35‰): Depending on species, seagrasses could stand a salty environment up to 42‰ [27]. Euryhaline seagrass species, i.e.…”
Section: Seagrasses: Unique Origin Physiology and Performancesmentioning
confidence: 99%